STUDI KASUS : ASUHAN KEBIDANAN PADA Ny.W MASA KEHAMILAN TRIMESTER III, PERSALINAN, NIFAS, NEONATUS ,DAN KELUARGA BERENCANA : CASE STUDY: MIDWIFE CARE ON MY WHILE TRIMESTER III PREGNANCY, LABOR, NIFAS, NEONATES, AND FAMILY PLANNING - Nur Silvia; Norif Didik Nur Imanah; Yuli Sya’baniah; Ellyzabeth Sukmawati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Pregnancy, childbirth, newborns, postpartum, and until the mother decides to use family planning which aims to provide continuity of care services by assisting pregnant women until the family planning period by all elements in the community, including students. Students are expected to be able to provide comprehensive midwifery care to mothers starting from pregnancy, childbirth, newborns, postpartum and family planning. In this case study, the author uses descriptive research methods with data collection techniques in the form of primary data (anamnesis, physical examination) according to Varney's 7-step management and secondary data (MCH book, client's medical records). Documentation of research results using the Varney and SOAP methods. Based on a comprehensive assessment of midwifery care for Mrs. W, starting from pregnancy, childbirth, postpartum and newborn, as well as family planning, there was no data that referred to an emergency or pathology, the mother and baby were in physiological condition. From the results of this case study, it can be concluded that comprehensive midwifery care for Ny. W have been done starting from pregnancy, childbirth, postpartum, newborn and family planning there are some gaps between theory and practice but there are no complications